Mohamad Zaid Bin Mustafa1 MohdNorazmi Bin Nordin2 Abdul Rasid Bin Abdul Razzaq3 Badaruddin bin Ibrahim4 - Chumki Handique (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
This study examines the impact of internet use and expenditure on R&D activities on the economic growth of India. We used time series data for the period 1995 to 2018 in our analysis. We formulated an economic growth model following the works of Romer and Barro. The model comprises of three more variables other than internet users and R&D expenditure. Using econometric estimation techniques like Augmented Dicky Fuller unit test, Johansen Co-integration, Durbin-Watson correlation test and time-series regression estimation, we found a strong long run association between the variables. Results indicate that there exists a positive and significant impact of internet use and R&D expenditure in strengthening the growth of a developing country like India.